2006
DOI: 10.1111/j.1464-410x.2006.05999.x
|View full text |Cite
|
Sign up to set email alerts
|

A new fast‐melting oral formulation of desmopressin: a pharmacodynamic study in children with primary nocturnal enuresis

Abstract: OBJECTIVE To determine the pharmacodynamic properties of a new oral lyophilisate formulation of desmopressin (in single doses of 30, 60, 120, 240, 360 or 480 µg) in children with known primary nocturnal enuresis (PNE) and thus identify those dosages that could provide a duration of action corresponding to a typical length of night‐time sleep in children with PNE; additional objectives were to determine the safety and tolerability of desmopressin in this population. PATIENTS AND METHODS Children with PNE (mean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(42 citation statements)
references
References 14 publications
1
36
0
3
Order By: Relevance
“…With respect to the comparison of tablets and sublingual lyophilisate, no significant differences in outcome resulted [22,43]. Our review did not show differences in the tolerability profile of desmopressin comparing the different routes of application.…”
Section: Desmopressin Treatment Regimenmentioning
confidence: 47%
“…With respect to the comparison of tablets and sublingual lyophilisate, no significant differences in outcome resulted [22,43]. Our review did not show differences in the tolerability profile of desmopressin comparing the different routes of application.…”
Section: Desmopressin Treatment Regimenmentioning
confidence: 47%
“…A high inter-and intra-individual variation in PK/PD has been seen with the sublingual administration of desmopressin [10,11], and the intravenous infusion was chosen to minimize these variations. However, this study also showed a wide variation with the i.v.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical data were derived from a PD double-blind, randomised, parallel-group study in children and adolescents with primary MNE [14].…”
Section: Methodsmentioning
confidence: 99%
“…The study design and the clinical and safety results of this study have been reported in detail elsewhere [14]. Briefly, eligible patients were randomised to either placebo or one of six single doses of 30, 60, 120, 240, 360 or 480 μg desmopressin.…”
Section: Methodsmentioning
confidence: 99%